2007
DOI: 10.1097/mao.0b013e31814b2787
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vascular Endothelial Growth Factor and Basic Fibroblast Growth Factor in Sporadic Vestibular Schwannomas Correlates to Growth Characteristics

Abstract: The bFGF and VEGF mRNA expression and the bFGF and VEGF protein expression in sporadic VS correlates to the tumour volume, to the tumor growth index, and to the MVD. This might indicate an angiogenic and neurotrophic influence of these factors and a possible involvement in the growth of sporadic VS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 18 publications
4
43
0
Order By: Relevance
“…Moreover, we found that all of the tumors expressed VEGFR-1/Flt and VEGFR-2/Flk as well as the coreceptor NP1. Expression of VEGF and of all three receptors was identified both on tumor cells and on endothelial cells of tumor-associated vessels, which is in line with previous reports [5,7,26,27]. This finding may suggest a cross-talk between tumor cells and vessels in a paracrine-stimulating manner.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Moreover, we found that all of the tumors expressed VEGFR-1/Flt and VEGFR-2/Flk as well as the coreceptor NP1. Expression of VEGF and of all three receptors was identified both on tumor cells and on endothelial cells of tumor-associated vessels, which is in line with previous reports [5,7,26,27]. This finding may suggest a cross-talk between tumor cells and vessels in a paracrine-stimulating manner.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, VEGF has been reported to act as a survival factor for Schwann cells [10]. Accordingly, upregulated VEGF expression has been previously demonstrated in VS [5,7,24,25,26]. In our present study also, all samples expressed VEGF.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Schwannomas do not harbor the bcr-abl oncogenic translocation, but expression of PDGFRs and growth factors has been previously noted (13)(14)(15)(16)(17)(18). To determine if c-kit, PDGFR-α, and PDGFR-β are expressed, activated, and play a functional role in promoting growth, we used human surgical schwannoma specimens as well as the HEI-193 immortalized human schwannoma cell line.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to initiation, the molecular factors that promote the usual indolent growth of schwannomas and the occasional growth spurts are not well studied. Aberrant expression and activation of growth factors and receptors are prime candidates and are potential biological targets, which may be therapeutically exploited to either negate or delay active intervention in selected cases (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%